Influência das características do Itabirito concentrado no desempenho do processo de sinterização - Lindaura de Souza Candido D'avila (2015)
In recent years the iron ore deposits have identified strong changes in the profile of ROM (Run of Mine) that feeds the processing plants. The relationship hematite/Itabirite (HE/IT) in ROMs, over time has become smaller and smaller, and this reduction is a direct result of a more itabiritic ROM compared to the last decade. The reversal of thisrelationship is a natural tendency of reserves or deposits with the evolution of mining, and increased participation of itabirite in the matrix of iron ores which are fed in the beneficiation plants, it becomes increasingly important to know the behavior of these iron ore to maintain the productivity of the Sintering Plants. Within this reality of elevation of the use of iron ore itabiritic, this study aimed to investigate the characteristics and performance in sintering pilot scale of that iron ore. It was initially characterized the hematite iron ore and itabiritic coming from theQuadrilátero Ferrífero. For physical characterization of iron ore, tests were carried out to evaluate cold agglomeration power, ability to humidification by the effect of capillary pressure of iron ore, porosity through specific-gravity bottle, determining the angle of repose of iron ore and grain size analysis. Then iron ore mixtures were tested in pilotscale with varying proportions of hematite and itabirite ore. The sinters generated from the mixtures were tested for chemical, physical and metallurgical quality. From the productivity and quality sinter results obtained it was possible to evaluate the effect of the itabiritic ore on the sintering mix. These results indicate different performance ofthese parameters in pilot sinter plant. The studied iron ores have chemical and mineralogical distinctions regarding their characterization. The itabiritic iron ore presented a higher content of contaminants, especially silica, which was 6.41%, whereas the hematite presented only 0.92%. In hematite iron ore, it was observed that hematite lobular is the predominant mineral phase, while in itabiritic iron ore, the main phase found is magnetite. Significant differences were also observed related to the physical characteristics of these ores. Compared to hematite iron ore, itabiritic iron ore presented higher porosity values, which should explain their less cold agglomeration performance and greater capacity for humidification in the tested conditions. It was also observed that the performance of the sintering process was influenced by the intrinsic characteristics of ores, such as, mineralogical, and physical characteristics. The best productivity levels were obtained in the pilot sintering plant with hematite iron ore.